PENGARUH CARA PENGERINGAN TERHADAP PEROLEHAN EKSTRAKTIF, KADAR SENYAWA FENOLAT DAN AKTIVITAS ANTIOKSIDAN DARI DAUN DEWA (Gynura pseudochina (L.) DC.) - Harrizul Rivai; Hazli Nurdin; Hamzar Suyani; Amri Bakhtiar (Faculty of Pharmacy, Universitas Gadjah Mada, 2010)
Effects of drying methods in gaining of extractive, phenolic content and antioxidant activity in Gynura pseudochina (Lour.) DC leaves have been investigated. The drying methods tested were air-drying at ± 25 oC, oven-drying at 40 OC, oven-drying at 60 OC, microwave oven-drying and fresh samples as control. Results revealed that drying of the fresh plant caused the decrease of extractive obtainability, phenolic content and antioxidant activity. There were significant differences among drying methods (P < 0.05). Among the drying methods tested, the highest extractive obtainability was by microwave oven-drying, whereas the highest phenolic concentration and antioxidant activity were by air-drying at ± 25 oC.